2021
DOI: 10.3390/cancers13122990
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Genetic Associations between Alzheimer’s Disease, Parkinson’s Disease, and Cancer

Abstract: Alzheimer’s (AD) and Parkinson’s diseases (PD) are the two most prevalent neurodegenerative disorders in human populations. Epidemiological studies have shown that patients suffering from either condition present a reduced overall risk of cancer than controls (i.e., inverse comorbidity), suggesting that neurodegeneration provides a protective effect against cancer. Reduced risks of several site-specific tumors, including colorectal, lung, and prostate cancers, have also been observed in AD and PD. By contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 109 publications
0
30
0
Order By: Relevance
“…Looking at Table 2 , we see that the same topic is also enriched in keywords associated to Alzheimer disease. Indeed, it is known that there is a sort of inverse comorbidity [ 48 ] between a few types of cancer (in particular, lung [ 49 ] and breast [ 50 ]) and Alzheimer’s disease. This association is confirmed and supported by our analysis, which also suggests that it could be mediated exactly by the microRNAs contained in miRNA-topic 7.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at Table 2 , we see that the same topic is also enriched in keywords associated to Alzheimer disease. Indeed, it is known that there is a sort of inverse comorbidity [ 48 ] between a few types of cancer (in particular, lung [ 49 ] and breast [ 50 ]) and Alzheimer’s disease. This association is confirmed and supported by our analysis, which also suggests that it could be mediated exactly by the microRNAs contained in miRNA-topic 7.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at Table 2 we see that the same topic is also enriched in keywords associated to Alzheimer desease. Indeed it is known that there is a sort of inverse co-morbidity [48] between a few types of cancer (in particular lung [49] and breast [50]) and the Alzheimer desease. This association is confirmed and supported by our analysis, which also suggests that it could be mediated exactly by the microRNAs contained in miRNA-topic 7.…”
Section: Resultsmentioning
confidence: 99%
“…Parkinsons disease was enriched in the high-risk group. Foreś-Martos et al (88) demonstrated that significant genetic correlations exist between Parkinson's disease, prostate cancer, and melanoma.…”
Section: Discussionmentioning
confidence: 99%